Meaning, Frames, and Conceptual Representation - Gamerschlag, Thomas; Petersen, Wiebke; Osswald, Rainer; Gerland, Doris; Gamerschlag, Thomas; Petersen, Wiebke; Osswald, Rainer; Gerland, Doris (De Gruyter, 2021)
The articles in this volume present contemporary and original research on linguistic meaning, concept formation and conceptual analysis. A central theme across the articles is the question of how concepts are structured, how they are represented in the mind, and how they are expressed in language. Two introductory papers on concept types and frames set out the crucial role of attributes and frames for the representation of concepts. The topics of the contributions range from the interrelation between determination and reference of nominal expressions, the verbal and adjectival expression of attributes, and the analysis of metonymy to the frame-based representation of action-related concepts and the classification of mental disorders in psychiatry. The collection of articles provided by this volume will be of interest to researchers and advanced students in the fields of semantics, pragmatics, philosophy of mind, and the cognitive sciences.
English
Keywords: linguistics; Semantic Fields; Determination; Cognitive Frames; Concept Types